Comparison of the mRNA expression profile of B‐cell receptor components in normal CD5‐high B‐lymphocytes and chronic lymphocytic leukemia: a key role of ZAP70. (10th November 2017) - Gladkikh, Aleena A.; Potashnikova, Daria M.; Tatarskiy, Victor; Yastrebova, Margarita; Khamidullina, Alvina; Barteneva, Natasha; Vorobjev, Ivan
Abstract: The B‐cell receptor (BCR) signaling pathway is of great importance for B‐cell survival and proliferation. The BCR expressed on malignant B‐CLL cells contributes to the disease pathogenesis, and its signaling pathway is currently the target of several therapeutic strategies. Although various BCR alterations have been described in B‐CLL at the protein level, the mRNA expression levels of tyrosine kinases in B‐CLL compared to that in normal CD5‐high and CD5‐low B‐lymphocytes remain unknown. In the current study, we measured the mRNA expression levels of CD79A, CD79B, LYN, SYK, SHP1, and ZAP70 in purified populations of CD5‐high B‐CLL cells, CD5‐low B‐cells from the peripheral blood of healthy donors, and CD5‐high B‐cells from human tonsils. Here, we report a clear separation in the B‐CLL dataset between the ZAP70 ‐high and ZAP70 ‐low subgroups. Each subgroup has a unique expression profile of BCR signaling components that might reflect the functional status of the BCR signaling pathway. Moreover, the ZAP70‐ low subgroup does not resemble either CD5‐high B‐lymphocytes from the tonsils or CD5‐low lymphocytes from PBMC ( P  < 0.05). We also show that ZAP70 is the only gene that is differentially expressed in CD5‐high and CD5‐low normal B‐lymphocytes, confirming the key role of Zap‐70 tyrosine kinase in BCR signaling alterations in B‐CLL. Abstract : We report that ZAP70 is expressed differentially in CD5‐positive and CD5‐negative B‐lymphocytes. Moreover, ZAP70 ‐high and ZAP70 ‐low subgroups of B‐CLL lymphocytes have unique expression profile of BCR signalosome genes. Our results can be used in broad clinical practice, providing a valuable tool for future therapeutic strategies' development.